2018
DOI: 10.1021/acsbiomaterials.8b00613
|View full text |Cite
|
Sign up to set email alerts
|

Toll-like Receptor 2-Dependent NF-κB/AP-1 Activation by Damage-Associated Molecular Patterns Adsorbed on Polymeric Surfaces

Abstract: The foreign body reaction is a chronic inflammatory response to an implanted biomaterial that ultimately leads to fibrous encapsulation of the implant. It is widely accepted that the host response to implanted biomaterials is largely dependent on the species and conformations of proteins adsorbed onto the material surface due to the adsorbate's role in mediating cellular interactions with the implanted material. While the cellular response to adsorbed serum-derived proteins has been studied extensively, the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 67 publications
3
26
0
Order By: Relevance
“…The COOH surfaces also adsorbed relatively less pro-inflammatory proteins than the NH 2 and TCPS surfaces from the medium. A previous report showed that the relative amount of adsorbed DAMPs was related to the extent of NF-κB activity and pro-inflammatory responses, and this suggests that the reduced presence of DAMPs on COOH surfaces could have helped reduce the pro-inflammatory macrophage responses . Interestingly, there were no significant differences in some proteins that have been cited for their role in the immune response, such as immunoglobulins and complement proteins (see Table S2 for all one-way ANOVA results). , …”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…The COOH surfaces also adsorbed relatively less pro-inflammatory proteins than the NH 2 and TCPS surfaces from the medium. A previous report showed that the relative amount of adsorbed DAMPs was related to the extent of NF-κB activity and pro-inflammatory responses, and this suggests that the reduced presence of DAMPs on COOH surfaces could have helped reduce the pro-inflammatory macrophage responses . Interestingly, there were no significant differences in some proteins that have been cited for their role in the immune response, such as immunoglobulins and complement proteins (see Table S2 for all one-way ANOVA results). , …”
Section: Resultsmentioning
confidence: 77%
“…A previous report showed that the relative amount of adsorbed DAMPs was related to the extent of NF-κB activity and pro-inflammatory responses, and this suggests that the reduced presence of DAMPs on COOH surfaces could have helped reduce the proinflammatory macrophage responses. 63 Interestingly, there were no significant differences in some proteins that have been cited for their role in the immune response, such as immunoglobulins and complement proteins (see Table S2 for all one-way ANOVA results). 11,21 From the initial list of proteins, we narrowed our search using the Gene Ontology database to find proteins under the cellular component category of extracellular region since we wanted to understand the role of proteins that are typically found outside the cells; the number found in the extracellular region for each surface is also listed in Table 3.…”
Section: M0 Macrophage Response To Inflammatory Stimulation Ismentioning
confidence: 94%
“…Khan et al [ 15 ] showed that Anomalin could inhibit AP-1 to relieve mechanical pain and inhibit leukocyte infiltration in ALI rats. And AP-1 is regulated by TLR2 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Understanding how the body recognizes and reacts to the implanted biomaterials has been considered to be a “holly grail” of biomaterial science, as it may lead to approaches that minimize chronic inflammatory response and ultimately minimized fibrosis. In this issue, Lindsay Fitzpatrick’s laboratory delineates a mechanism of recognition, by the Toll-like receptors, of damage-associated molecular patterns adsorbed on polymeric surfaces …”
mentioning
confidence: 99%
“…In this issue, Lindsay Fitzpatrick's laboratory delineates a mechanism of recognition, by the Toll-like receptors, of damage-associated molecular patterns adsorbed on polymeric surfaces. 17 Canadian scientists are also leading in the development of smart food packaging that can inform us on the state of the food inside the package or keep the food fresh without adding preservatives to it. In the future, it might be possible for the packaging material to warn us when the food inside has gone bad or become contaminated with bacteria, potentially saving lives.…”
mentioning
confidence: 99%